PENGARUH TINGKAT PROFIABILIAS, LIKUIDITAS, LEVERAGE, UKURAN PERUSAHAAN DAN UMUR PERUSAHAAN TERHADAP PENGUNGKAPAN ISLAMIC SOCIAL REPORTING PADA PERBANKAN SYARIAH INDONESIA TAHUN 2010-2014 - LESTARI, SANTI (Jurnal Akuntansi AKUNESA, 2016)
This research is aimed to analyse of the profitability, liquidity, leverage, company size, company age influences to disclosure ISR. The population that is used in this research is syariah bank in Indonesia listed in BUS at  2010-2014 period. Determining the of sample uses purposes sampling technique. The number of sample are 8 of BUS. The data uses in this reseacrh is annual report or suistanable report in each of syariah banking. Analysis that is used in this research consists of analysis content hypothesis examining with multiple linear regresion. The results showed that the profitability, liquidity, leverage and company size doesn’t have significant effect to Islamic Social Reporting (ISR) disclosure. While for the company ege variables had significant effect to Islamic Social Reporting (ISR) disclosure.